Traditional Jones criteria: limitation in the diagnosis of rheumatic fever in patients with mitral valve repair - Yubbu, Putri; Jamaluddin, Johan Aref; Chang, Lydia Munn Ying; Kandavello @ Kandhavel, Geetha; Alwi, Mazeni; Samion @ Mingan, Hasri; Othman, Norlijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
The present study aims to determine the limitations of traditional Jones criteria during the first episode of acute rheumatic fever (ARF) at the initial referral hospital, in a cohort of patients below 18 years old who had undergone mitral valve repair in National Heart Institute (IJN) from 2011 to 2016. Carditis followed by fever and joint involvement were the most frequent manifestations at first diagnosis. Of the 50 patients, only seven (14%) fulfilled the traditional Jones criteria for the diagnosis of the first episode of ARF. When compulsory evidence of a previous group A Beta hemolytic streptococcus (GABHS) was disregarded, this figure rose to 54%. Therefore, strict adherence to Jones criteria with absolute documentation of GABHS will lead to underdiagnoses of ARF. The application of echocardiographic diagnostic criteria of rheumatic heart disease (RHD) needs to be emphasized to allow early diagnosis and administration of secondary prophylaxis to prevent progression to severe valvular disease.